Improvement of ɣ-Aminobutyric acid production and cell viability of Lactiplantibacillus plantarum B7 via Whole-Cell immobilisation in repeated batch fermentation system - Pannerchelvan, Sangkaran; Muhamad, Faris Nulhaqim; Wasoh, Helmi; Mohamed, Mohd Shamzi; Faizal Wong, Fadzlie Wong; Mohamad, Rosfarizan; Halim, Murni (Springer, 2023)
Whole-cell immobilisation technology involving ℽ-aminobutyric acid GABA biosynthesis using lactic acid bacteria (LAB) has been extensively studied owing to its numerous benefits over free-living bacteria, including enhanced productivity, improved cell viability, ability to prevent cell lysis and protect cells against bacteriophages and other stressful conditions. Therefore, a novel LAB biocatalyst was developed using various fruit and fruit waste, immobilising a potential probiotic strain, Lactiplantibacillus plantarum B7, via an adsorption method to improve GABA and cell viability. Apple and watermelon rind have been known to be the ideal natural supports for L. plantarum B7 owing to higher GABA and lactic acid production and improved cell viability among the other natural supports tested and selected to be used in repeated batch fermentation (RBF) to improve GABA production and cell viability. In general, immobilisation of L. plantarum B7 on natural support has better GABA and lactic acid production with improved cell viability via RBF compared to free cells. Watermelon rind-supported cells and apple-supported cells could produce nine and eight successful GABA cycles, respectively, within RBF, whereas free cells could only produce up to four cycles. When using watermelon rind-supported cells and apple-supported cells in RBF, the GABA titer may be raised by up to 6.7 (218.480 ± 0.280 g/L) and 6 (195.439 ± 0.042 g/L) times, respectively, in comparison to GABA synthesis by free cells in single batch fermentation (32.65 ± 0.029 g/L). Additionally, natural support immobilised L. plantarum B7 could retain half of its cell viability even after the 12th cycle of RBF, while no cell was observed in control.